Affective-semiotic universe of adolescents within restrictive of freedom socio-educational sanction (Educação e Pesquisa, 2020)
The Statute of Child and Adolescent (BRAZIL, 1990) affirms the shared responsibility of the State, families and society regarding the protection of Brazilian children’s and youth’s rights. After the due process, adolescents who have provenly committed illegal acts are submitted to a set of social-educational measures which aim at promoting his/her development and full social integration. The guidelines for such social pedagogical work presuppose a critical criminology approach. Nevertheless, criminalization of poverty is a historic and ideological rooted feature in Brazilian culture. Based on the theoretical framework of critical criminology, more specifically on the concept of criminalization of poverty, and on cultural psychology, this paper analyzes the affective-semiotic universe that pervades the lives of adolescents who are complying with internment socio-educational measures. As an illustration of the theoretical elaborations, we have analyzed written chronicles and oral narratives produced by adolescents who participated in a dialogue circle in a detention center in Brasilia, Brazil. This material was obtained within supervised training activities held by undergraduate Psychology students and evidences the semiotic work operated by socio-educational system in which education – as an emancipatory practice, oriented to the building of other future possibilities and new biographical trajectories – is substituted by an emphasis on the dangerousness of adolescents. In this semiosphere, the signs express depreciative and condemnatory beliefs. These dialogue circles turned out to be be favorable spaces that enable people to overcome the stigma attached to the youth offenders who are labeled as criminals, through the discourse of criminalization of poverty.